Zinc Ion Removal on Hybrid Pectin-Based Beads Containing Modified Poly(Methyl Methacrylate) Waste - Jakóbik-Kolon, Agata (Molecules, 2017)
A new hybrid sorbent in the form of round beads containing modified poly(methyl methacrylate) (PMMA) waste immobilized in pectin and crosslinked with calcium ions was prepared. A previously obtained and characterized powdered poly(methyl methacrylate)–based sorbent was used. Batch and column studies on the new material’s sorption-desorption properties were performed. Two kinetic models (pseudo-first- and pseudo-second-order) and three isotherms (Langmuir, Langmuir bisite and Freundlich) were used to describe the results. Breakthrough and elution curves were also obtained. Nitric, hydrochloric, and sulfuric acid of various concentrations were used in the desorption studies. Higher sorption affinity of zinc(II) ions to hybrid sorbent than to pectin alone, reflected by higher values of the Langmuir and Freundlich model parameters, was observed. The maximum sorption capacities, calculated based on the best-fitted models, were 50.2 mg/g (Langmuir bisite) and 42.2 mg/g (Langmuir) for hybrid and only pectin beads, respectively. The stripping of Zn ions using 0.1 M solutions of mineral acids was similarly effective in the case of both sorbents. The mass balance calculated for the column studies showed about 100% recovery of zinc in a sorption-desorption cycle. By applying the hybrid sorbent under the studied conditions it is possible to purify Zn in water to the level permitted by law and concentrate Zn(II) ions by about 60 times.